Enforcement of Labor Regulation, Informal Labor, and Firm Performance - Almeida, Rita; Carneiro, Pedro (World Bank, Washington, DC, 2012)
This paper investigates how enforcement of labor regulation affects the firm's use of informal employment and its impact on firm performance. Using firm level data on informal employment and firm performance, and administrative data on enforcement of regulation at the city level, the authors show that in areas where law enforcement is stricter firms employ a smaller amount of informal employment. Furthermore, by reducing the firm's access to unregulated labor, stricter enforcement also decreases average wages, productivity, and investment. The results are robust to several specification changes, and to instrumenting enforcement with (1) measures of access of labor inspectors to firms, and (2) measures of general law enforcement in the area where the firm is located.